WAJAH BARU GERAKAN DAKWAH KAMPUS (GERAKAN TARBIYAH) ERA SEKARANG - Fadilah, Rizki Nur; Lestari, Tilas; Faizah, Az-Zafira Syairul; Hidayatullah, Ahmad Fauzan (Jurnal Dakwah Tabligh, 2020)
The campus propaganda movement began with a movement carried out by students of the Salman ITB Mosque spearheaded by Indonesian students studying in Egypt. These Egyptian alumni learned from the Ikhwanul Muslimin and they taught their knowledge and experiences in Indonesia country after they go home to Indonesia country. The Tarbiyah Movement which is currently transforming into the Justice Party then becomes the Social Justice Party (PKS). The change to PKS was a result of the opening of public space after the falling of President Soeharto. After being transformed into a political party, is this campus Da'wah Movement still following the ideology of the Ikhwanul Muslimin and to find out why the campus missionary movement is transforming into PKS. This is our reason to write this journal. The method used in this research is a literature study, analytical descriptive, and comparative. The results of this study were produced from surgical journals and theses.